Concomitant KRAS and BRAF mutations in colorectal cancer - Midthun, Lauren; Shaheen, Shagufta; Deisch, Jeremy; Senthil, Maheswari; Tsai, James; Hsueh, Chung-Tsen (Journal of Gastrointestinal Oncology; Vol 10, No 3 (June 01, 2019): Journal of Gastrointestinal Oncology, 2019)
BRAF and KRAS are two key oncogenes in the RAS/RAF/MEK/MAP-kinase signaling pathway. While previously considered mutually exclusive, concomitant mutations in both KRAS and BRAF genes have been identified in colorectal cancer (CRC). The clinical outcome of these patients remains undetermined. We present the clinical course of two patients with CRC harboring mutations at codon 12 of KRAS and BRAF non-V600E mutations. More research is needed to determine the clinical-pathological effect of these simultaneous mutations of KRAS and BRAF in CRC on disease course and treatment outcome.